TOKEK SEBAGAI METAFOR MANUSIA DALAM KARYA GRAFIS DENGAN TEKNIK RELIEF PRINT - Rahmat Rahmat; Yofita Sandra (Serupa The Journal of Art Education, 2020)
The creation of this final work aims to visualize human social life in the form of a metaphor a concept of graphic art. This Creator Showing various forms of social life in the metaphor contain society. The methods and processes of work used in the creation of graphic art work go through several stages: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Realization Concepts, (5) Completion. The results of visualization of Gecko as a Human Metaphor in Relief Print with 10 titles: (1) Solitary, (2) Life, (3) Biggest, (4) Defense, (5) Cannibal, (6) Greedy, (7) Disguised, (8) Growing, (9) Different, (10) Self Identity.Keywords: Gecko, Metaphor, Graphic Art.